Chapter The impact of public research expenditure on agricultural productivity: evidence from developed European countries - Magrini, Alessandro (Proceedings e report, 2021)
The objective of this paper is to assess the impact of public research expenditure on agricultural productivity in developed European countries. Our research provides original evidence, making possible a comparison with existing studies focused on United States of America (USA). We apply a fixed effects Gamma distributed-lag model to yearly data in 1970-2016 sourced from the United States Department of Agriculture (USDA), the Organisation for Economic Cooperation and Development (OECD), and the Food and Agriculture Organization (FAO). In our results, public research expenditure has a significant impact on agricultural productivity up to 35 years, with peak at 17 years and long-term elasticity equal to 0.172. Based on our model, the countries with the highest internal rate of return of agricultural research expenditure resulted Germany, Spain, France and Italy (24.5-25.2%), followed by Netherlands, United Kingdom, Denmark, Greece, Belgium and Luxembourg (20.5-21.8%). However, only Germany, Denmark and Greece increased agricultural research expenditure in recent years. The estimated internal rates of return are in line with the ones reported by existing studies on USA, and they suggest that developed European countries, just like USA, could benefit from research investments in Agriculture to a much greater extent than they currently do.